Evaluation of groundwater quality for agricultural use in Balzar, province the Guayas, Ecuador - Zambrano, Leontes; Navarrete, Dioselina; Arce, Ángel; Chila, Marcos; Medina, Kleber; Centanaro, Athina (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Water is a natural and vital resource for living beings and ecosystems. Groundwater is of great importance for human consumption and agricultural activities, but over the years, it has become an increasingly scarce resource. The objective of this research was to evaluate the quality of groundwater extracted from wells used for crop irrigation in Balzar, province the Guayas, Ecuador. Four treatments and three repetitions were used; groundwater extracted from three wells plus a distilled water core. Physical, chemical, microbiological analyzes and a toxicity test with dark incubation were carried out on seeds of radish (Raphanus sativus), cocoa (Theobroma cacao) and corn (Zea mays). Turbidity exceeded permitted levels under TULSMA regulations and bicarbonate and chlorine levels exceeded the permitted limit. The microbiological analysis reflected fecal coliform values above 1000 UFC.100 mL-1 of water, indicating the presence of contaminants in the water sources. Phytotoxicity tests carried out with radish seeds showed a stimulation of radicle growth in well one and mild toxicity in wells two and three. For cocoa and corn seeds, moderate and mild toxicity was evident, respectively in the three wells. Although the maximum permissible limits were exceeded in some variables, the water from the three wells can be used for irrigation; however, there is a need to take measures to improve the quality of the water in these wells.